VYTAUTAS KINDURYS. LIFE INSURANCE BUSINESS AND ITS DEVELOPMENT TENDENCIES AND MANIFESTATIONS IN LITHUANIA: THEORETICAL AND PRACTICAL ASPECTS - Mackevičius, Jonas (Ekonomika, 2011)
The monograph. Vilnius: Vilnius University Publishing House, 2011, 558 p.